Gain-of-Function Mutations R249C and S250C in Complement C2 Protein Increase C3 Deposition in the Presence of C-Reactive Protein - Urban, Aleksandra; Kowalska, Daria; Stasiłojć, Grzegorz; Kuźniewska, Alicja; Skrobińska, Anna; Arjona, Emilia; Alonso, Eugenia Castellote; Fenollosa Segarra, María Ángeles; Jongerius, Ilse; Spaapen, Robbert; Satchell, Simon; Thiel, Marcel; et al. (Frontiers in Immunology, 2021)
Atypical hemolytic uremic syndrome (aHUS) and C3 glomerulopathy (C3G) are rare kidney diseases fueled by the impairment of the alternative complement pathway. We recently described an aHUS patient carrying an exceptional gain-of-function (GoF) mutation (S250C) in the classical complement pathway component C2 leading to the formation of hyperactive classical convertases. We now report the identification of the same mutation and another C2 GoF mutation R249C in two patients with C3G. Both mutations stabilize the classical C3 convertases by a similar mechanism and result in increased deposition of C3 on glomerular endothelial cells exposed to human serum supplemented with C-reactive protein. Our data justify the inclusion of classical pathway genes in the aHUS/C3G genetic analysis and identify antibody-independent triggers of complement dysregulation in carriers of these C2 variants.